2019
DOI: 10.1136/bmjopen-2018-021529
|View full text |Cite
|
Sign up to set email alerts
|

Under-reporting of diagnosed tuberculosis to the national surveillance system in China: an inventory study in nine counties in 2015

Abstract: ObjectiveThe WHO estimates that almost 40% of patients diagnosed with tuberculosis (TB) are not reported. We implemented this study to assess TB under-reporting and delayed treatment registration in nine counties in China.DesignA retrospective inventory study (record review).SettingCounties were selected using purposive sampling from nine provinces distributed across eastern, central and western regions of China in 2015.Primary and secondary outcome measuresUnder-reporting was calculated as the percentage of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 20 publications
4
37
0
1
Order By: Relevance
“…The Chinese law on infectious diseases requires that PTB, but not extrapulmonary TB (EPTB) be notified. Second, child patients with TB are treated at paediatric hospitals or large general hospitals, which are not directly linked to the TBIMS 16 17. Third, although we believed that many child TB, especially EPTB cases are not reported in China, the actual proportion may be less than 6% after 2010 18 19.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese law on infectious diseases requires that PTB, but not extrapulmonary TB (EPTB) be notified. Second, child patients with TB are treated at paediatric hospitals or large general hospitals, which are not directly linked to the TBIMS 16 17. Third, although we believed that many child TB, especially EPTB cases are not reported in China, the actual proportion may be less than 6% after 2010 18 19.…”
Section: Discussionmentioning
confidence: 99%
“…A special module in TBIMS acts as an interface between TBIMS and IDRS, and information for one case can be simultaneously updated in these two systems. However, under-reporting of diagnosed TB has also existed in China [14]. A recent retrospective inventory studies conducted in nine counties, by reviewing medical records at the participating health facilities and county-level social insurance system databases, reported that nearly 20% of TB patients were not reported to TBIMS, being higher percentage for children with TB, TB pleurisy, patients diagnosed in the eastern and central regions and patients with a TB diagnosis recorded in either health facilities or social insurance system [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In a report published in 2015, IDRS covered all provincial, prefectural, and county CDCs, 98% of medical institutions at or above the county administrative level, and 94% of community medical institutions [11]. TBIMS is the surveillance system for the national TB program (NTP) and is used for managing the full course of treatment of PTB patients, and does not capture information on TB presumptive patients [12]. TBIMS is accessible by all government-appointed TB-designated facilities, which could be local CDCs, TB dispensaries or TB-designated hospitals [12].…”
Section: Introductionmentioning
confidence: 99%
“…TBIMS is the surveillance system for the national TB program (NTP) and is used for managing the full course of treatment of PTB patients, and does not capture information on TB presumptive patients [12]. TBIMS is accessible by all government-appointed TB-designated facilities, which could be local CDCs, TB dispensaries or TB-designated hospitals [12]. These two systems are independent, but there is a function within the systems to link information about patients diagnosed with TB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation